The Role of Social Media Usage on Entrepreneurship Orientation and MSME’s Performance - Siswandi Liswoyo; Lydiawati Soelaiman (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this study was to determine whether there is an influence of entrepreneurship orientation on the performance of MSMEs in Jakarta mediated using social media. The non-probability sampling technique is used in the sample selection process. The sampling technique uses purposive sampling and snowball sampling methods. In this study, data was collected by distributing online questionnaires in the form of a google form so that as many as 101 respondents were obtained from MSME in Jakarta. Data were processed using PLS-SEM method. Based on the findings of this research, entrepreneurship orientation has no significant effect on MSME business performance in Jakarta; however, using social media can fully mediate the significant effect of entrepreneurship orientation on MSME’s performance in Jakarta.